TANTANGAN DALAM MENGEMBANGKAN JIWA ENTREPRENEUR DI KALANGAN GENERASI MUDA WIRAUSAHA BULELENG BALI (Manajemen & Bisnis Jurnal, 2020)
This study aims to determine the challenges in developing the spirit of entrepreneurship among the young generation of entrepreneurs in Bali Buleleng. The method is through interviews with several young entrepreneurs who are struggling in various fields of business. The results obtained that every person has an entrepreneurial spirit that is able to form independence in developing potential, creativity, discipline and responsibility with initiative and innovative use of economic resources that are owned in order to develop businesses to earn income. Various efforts carried out by young entrepreneurs provide various types of challenges that encourage entrepreneurs to continue to develop. These challenges include market competition, work productivity, and product innovation.